Anogenital warts in children: sexual abuse or unintentional contamination? - Lisieux Eyer de Jesus; Oscar Luís Lima e Cirne Neto; Leila Maria Monteiro do Nascimento; Rejane Costa Araújo; Andréa Agostinho Baptista
Anogenital warts (AGW) were recently recognized in children, and their significance as an index of childhood sexual abuse is controversial. We report our transdisciplinary approach (including a pediatric surgeon, psychologist, social worker, ethics expert, and occasionally law enforcement agents) and its results in a group of 17 children with AGW treated at the public pediatric referral hospital in Rio de Janeiro, Brazil, during a 3-year period (1996-1999). All children were treated by electrocauterization of the warts, tested for other STDs, and submitted to perineal examination under anesthesia. Families received psycho-social counseling as necessary and cases were referred to child protection and law enforcement agents when indicated according to Brazilian legislation. We identified a high incidence of sexual abuse (8 children, 5/7 > 5 years old), with 3 patients inconclusive as to sexual abuse and 7 cases of perinatal transmission (5/8 < 4 years old). We conclude that AGW are indeed a strong sign of suspicion for sexual abuse in children, especially but not exclusively > 5 years of age. However, strong support and a transdisciplinary approach to the children and their families is necessary to identify it.